Exercise-induced signaling pathways to counteracting cardiac apoptotic processes - Pahlavani, Hamed Alizadeh (Frontiers in Cell and Developmental Biology, 2022)
Cardiovascular diseases (CVDs) are the most common cause of death in the world. One of the major causes of cardiac death is excessive apoptosis. However, multiple pathways through moderate exercise can reduce myocardial apoptosis. After moderate exercise, the expression of anti-apoptotic proteins such as IGF-1, IGF-1R, p-PI3K, p-Akt, ERK-1/2, SIRT3, PGC-1α, and Bcl-2 increases in the heart. While apoptotic proteins such as PTEN, PHLPP-1, GSK-3, JNK, P38MAPK, and FOXO are reduced in the heart. Exercise-induced mechanical stress activates the β and α5 integrins and subsequently, FAK phosphorylation activates the Akt / mTORC1 and ERK-1/2 pathways, leading to an anti-apoptotic response. One of the reasons for the decrease in exercise-induced apoptosis is the decrease in Fas-ligand protein, Fas-death receptor, TNF-α receptor, Fas-associated death domain (FADD), caspase-8, and caspase-3. In addition, after exercise mitochondrial-dependent apoptotic factors such as Bid, t-Bid, Bad, p-Bad, Bak, cytochrome c, and caspase-9 are reduced. These changes lead to a reduction in oxidative damage, a reduction in infarct size, a reduction in cardiac apoptosis, and an increase in myocardial function. After exercising in the heart, the levels of RhoA, ROCK1, Rac1, and ROCK2 decrease, while the levels of PKCε, PKCδ, and PKCɑ are activated to regulate calcium and prevent mPTP perforation. Exercise has an anti-apoptotic effect on heart failure by increasing the PKA-Akt-eNOS and FSTL1-USP10-Notch1 pathways, reducing the negative effects of CaMKIIδ, and increasing the calcineurin / NFAT pathway. Exercise plays a protective role in the heart by increasing HSP20, HSP27, HSP40, HSP70, HSP72, and HSP90 along with increasing JAK2 and STAT3 phosphorylation. However, research on exercise and factors such as Pim-1, Notch, and FAK in cardiac apoptosis is scarce, so further research is needed. Future research is recommended to discover more anti-apoptotic pathways. It is also recommended to study the synergistic effect of exercise with gene therapy, dietary supplements, and cell therapy for future research.